Identifikasi Lapisan Akuifer Air Tanah menggunakan Metode Resistivitas di Dusun Puaringan, Desa Pelangan, Lombok Barat - Erintina, Melinda Dwi; Sismanto, Sismanto; Ubaidillah, Aji Syailendra; Hidayat, Syamsul; Faesal, Andi; Munarfan, ZA; Hermansyah, Wahyu; Syarbini, Khatib; Dermawan, Iwan; Anggraeni, Juraedah Dwi; Gunawan, Hendra (Jurnal Ilmiah Giga, 2025)
The aim of this study is to identify the groundwater aquifer layer using the resistivity method in Puaringan, Pelangan Village, West Lombok. The aquifer layer is a layer of rock that has the ability to store groundwater well. This layer also tends to have high porosity so that fluid/water is trapped in the layer. The resistivity method used is vertical electric sounding (VES). This method is effective in detecting the subsurface vertically. Data acquisition was carried out using two sounding points (S1 and S2). Sounding points S1 and S2 were processed using IP2WIN software to produce a picture of the subsurface rock layer. The results of the S1 point study showed that the groundwater aquifer layer was at a depth of 113-126 meters identified as a sandstone layer. The results of the S2 point study showed that the groundwater aquifer layer was at a depth of 105-198 meters identified as a sandstone layer.